Early Nutrition Intervention Attenuates Weight Gain for Pediatric Acute Lymphoblastic Leukemia Patients in Maintenance Therapy. Issue 2 (March 2018) - Hill, Rachel; Hamby, Tyler; Bashore, Lisa; Rapisand, Stefanie; Galipp, Kari; Heym, Kenneth; Bowman, W. Paul
Abstract : Obesity following treatment of pediatric acute lymphoblastic leukemia (ALL) has become a significant long-term concern. Excessive weight gain often occurs during treatment, particularly during induction and the first 6 months of maintenance therapy, and it may be potentially modifiable. This retrospective study aimed to evaluate the impact of an early, 3-visit nutrition intervention on weight gain during maintenance therapy in ALL patients. Medical records of the intervention group were compared with historical controls who were treated on the same ALL treatment protocols during an earlier time period. Anthropometrics were collected throughout intensive therapy and at every monthly visit during the first 12 months of maintenance therapy. In total, 67 patients were evaluated (33 in the intervention group and 34 in the control group). After controlling for significant predictors of body mass index (BMI) z -scores in maintenance therapy—including higher BMI at diagnosis and weight gain throughout intensive therapy—the intervention group demonstrated more controlled weight gain during maintenance therapy ( P <0.0001). A 3-visit nutrition intervention was effective in attenuating weight gain trends during ALL maintenance therapy. Abstract : Supplemental Digital Content is available in the text.